An analysis of the Hadith on Hajj Ifrad , as reported by Sunan Al-Nasā'ī, from a Sanadic Critique perspective - Amin, Hamma Aming; Syahputra, Arya; Rifai, Muhammad (Ihyaussunnah : Journal of Ulumul Hadith and Living Sunnah, 2023)
The main problem which is the focus point of this study is focused on the criticism of sanad, the purpose of which is to find out the truth of hadith from the point of view of authenticity and originality. Then the hadith scholars have attempted to classify and distinguish the hadiths that really come from the Prophet from human words that speak on behalf of the Prophet under the guise of false hadiths. Therefore, the presence of various terms or methods such as takhrij al-hadith greatly facilitates hadith reviewers in determining the status of hadith whether the hadith really originates from the Prophet or not. With this, it can be seen that the perfection of a hadith is if it fulfills the conditions, namely the sanad is continuous, narrated by a just person, narrated by a dhabit person, does not contain syadz or illat. The research method used is (library research) focused on books, books, journals, and applications such as Maktabah Syamilah, Hadis Shoft, Lidwa Pustaka, Tahzīb al-Kamāl fi al-Asmā' Rijāl, Tahzīb at-Tahzīb, Al-Mu'jam al-Mufahras li Alfādzi al-Hadīs al-Nabawī, and Mausu'ah al-Atrāf al-Hadīs al-Nabawī al-Syarīf. And the steps taken are using two takhrij methods 1) Takhrij by using the first pronunciation of the hadith matan, 2) Takhrij by using one of the pronunciations of the hadith matan.